(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an insightful overview of the recent reforms in the education system of Uzbekistan, underlining the nation’s commitment to modernization and development. It explores the key initiatives undertaken by the government to enhance the quality, relevance, and inclusivity of education, with a focus on promoting critical thinking and practical skills. The article also delves into the diverse landscape of educational institutions in Uzbekistan, spanning preschools, general education, vocational training, higher education, and specialized institutions. Through its comprehensive analysis, the article highlights Uzbekistan’s progress towards creating a dynamic education system that equips students with the tools they need to succeed in the 21st century.